2013
DOI: 10.1364/oe.21.026714
|View full text |Cite
|
Sign up to set email alerts
|

Bending effect on modal interference in a fiber taper and sensitivity enhancement for refractive index measurement

Abstract: We demonstrate the bending effect of microfiber on interference fringes in a compact taper-based modal interferometer and sensitivity for refractive index (RI) measurement. For the bend curvature ranging from 0 to 0.283 mm(-1), the measured RI sensitivity distinctively increases from 342.5 nm/RIU (refractive-index unit) to 1192.7 nm/RIU around RI = 1.333 and from 3847.1 nm/RIU to 11006.0 nm/RIU around RI = 1.430, respectively. Theoretical analysis reveals that such enhancement is determined by the dispersion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Its taper structure excites the higher‐order mode (HE 12 ), which interferes with the fundamental mode (HE 11 ), creating an interferometric fringe in the fiber transmission spectrum (Figure S3, Supporting Information) 22, 23. As the HE 12 mode spreads into the surface coating (Figure S4, Supporting Information), it senses the surface RI change and translates it into a wavelength shift in the interferometric fringe 12, 24.…”
Section: Resultsmentioning
confidence: 99%
“…Its taper structure excites the higher‐order mode (HE 12 ), which interferes with the fundamental mode (HE 11 ), creating an interferometric fringe in the fiber transmission spectrum (Figure S3, Supporting Information) 22, 23. As the HE 12 mode spreads into the surface coating (Figure S4, Supporting Information), it senses the surface RI change and translates it into a wavelength shift in the interferometric fringe 12, 24.…”
Section: Resultsmentioning
confidence: 99%
“…The evanescent wave micro-tapered fiber optical sensor was prepared as previously described by our group [24,25]: Briefly, a double cladded singlemode fiber was tapered down to micron scale in diameter by using a transverse scanning method. A flame with width of 5 mm scanned across the fiber once while slowly stretching the fiber with two linear stages.…”
Section: Sensing Principlementioning
confidence: 99%
“…Due to the relatively large index contrast between the core and cladding, the fiber allows well separation of the HE 11 and HE 12 modes to produce the π phase shift easily in the taper. The transition region acts as beam splitter/combiner while the uniform waist acts as the interferometer [24]. Normally, the external refractive index (RI) sensitivity of interferometer can be expressed by Formula (1) [21].…”
Section: Sensing Principlementioning
confidence: 99%
“…The maximum sensitivity was 44.26 pm= C between 20 C and 80 C, which was three to four times that of the unbent structure, because the asymmetrical modes excited by curved single-mode-multimode-single-mode structure were more sensitive to the ambient temperature. Sun et al [48] reported a high sensitivity refractive index sensor using a segment of bent taper fiber. This structure significantly enhanced the refractive index sensitivity due to the dispersion property of the intermodal index.…”
Section: Bendingmentioning
confidence: 99%